Agama Sebagai Faktor Konflik dan Integrasi - Muhamad Ali (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
Religion plays a crucial role in shaping social and individual life, even in secular states. In societies with a strong religious presence, such as Indonesia, religious institutions, figures, and symbols influence social interactions and national identity. However, religion presents a paradox: while it promotes peace and social cohesion, it has also been a catalyst for conflict and violence. This dual nature of religion raises essential questions about the conditions under which religion fosters integration versus when it becomes a source of division. This paper explores the complex relationship between religion, conflict, and social integration. It examines historical and contemporary cases where religion has both united and divided communities, highlighting the socio-political and ideological factors involved. The study also considers potential strategies for reducing religious conflict and fostering peaceful coexistence in the future.